ANALISIS KINERJA PENYULUH PERTANIAN DALAM MELAKSANAKAN TUPOKSI DI KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2017)
This study aims to analyze the performance of agricultural extension in Ulu Ogan Ogan. Research held in 5 BP3K (Agricultural Extension Centers Fisheries and Forestry) in the District OKU. The research method used in this research is the Survey method. Data method used is obervasi and interview with questioner as data collecting tool. the data used is primary data is data obtained directly from the field by using a questionnaire as a means of collecting data and secondary data is data obtained from the relevant agencies in this penelitin. Based on the results of research on Agricultural Extension Performance Analysis of Undertaking Auth in OKU District obtained results for Agricultural Extension Performance Existing In OKU District is amounting to 80.97%, the figure indicates that in general penyul uh Agriculture in the District OKU are in the Good category. Therefore the Overall Agricultural Extension Performance is Good.